Reaction to drought: A case study of native potatoes (Solanum spp.) cultivated in Huánuco, Perú - Egúsquiza Bayona, Rolando (2020)
Climate change is an obvious threat to agriculture, food security and conservation of plant genetic resources. Potato is a globally important food. In Peru, there is high variability and diversity of wild and cultivated species, such that they are considered as one of the region’s most vulnerable to the impact of climate change. With these considerations, we report the results of an investigation in which a preliminary screening of the reaction to drought of 67 native potato morphotypes was conducted to verify for differences in morphological indicators of growth, development, and production of tubers in response to continuous irrigation (CI) and restricted irrigation (RI) treatments. In the course of this study, 21 irrigations were applied to plants by CI (every 1-2 days) and, in the same period, 7 irrigations were applied to plants by RI (every 5-6 days). Comparison of characteristics average in all the morphotypes with plants under CI and RI, indicated that RI did not show differences in height of plants, length of internodes, or leaf and terminal leaflet indexes, and that RI reduced the stem thickness and dry weight of foliage. In this study, we highlight the morphotypes whose plant characteristics present higher averages with respect to their clonal counterparts that were treated with CI. The positive relationship between the number and weight of tubers harvested, as well as the significant reduction of both components of low RI yield is confirmed. In addition, we also highlight the response of some morphotypes that present higher tuber yield under RI. The native morphotypes that were identified as tolerant (according their responses in the characteristics of their plants and yield of tubers under RI) are as follows: BGR 19 (“Rayhuana”); BGR 99 (“Yuracc ñahui hualash”); BGR 170 (“Yana utcush”); and BGR 238 (“Muru huayro”).